Learning approach in engineering dynamics course of mechatronic engineering technology programme in theoretical and experimental learning scenarios - Hafizan Hashim; Noor Azean Anis Abd Aziz; Hanita Hashim (Penerbit Universiti Kebangsaan Malaysia, 2023)
How crucial are engineering mechanics courses for Mechatronic Engineering Technology Programme (METP)? Engineering dynamics is one of the mechanical fundamental courses taught in METP, UiTM Shah Alam, Malaysia. Teaching engineering mechanics courses can be challenging for several reasons: abstract concepts, math-intensive, and diverse backgrounds. Even though deep learning is mostly desirable in higher education, the learning scenarios can sometimes inspire different learning styles. The purpose of this study is to examine the learning approach adopted by mechatronic engineering technology students during engineering dynamics course in two learning situations: theoretical and experimental learning. Samples were recruited from the first cohort of METP students in UiTM. Online questionnaires that consist of revised R-SPQ-2F were distributed after completion of course assessment. Students were clustered into three types of learning approaches in the two scenarios: deep learning, mixed learning, and surface learning. Results showed that students from different backgrounds adopted different learning approaches in different scenarios. Factors such as previous institution, grade, and theoretical exposures play major roles in classifying students’ learning approaches. The study findings can help improve students’ learning approaches by specifically manipulating changes in the learning environment.